Detecção de defeitos em placas de circuito impresso aplicando visão computacional - Monteiro, Lucas Paiva (2023)
This work consists of the development of a vision system capable of identifying faults in printed circuit boards. The system consists of a 2MP high-speed camera, a camera controller to receive the image and apply computational vision tools, a PLC to process camera information and an HMI to serve as an interface for the test operator, allowing a monitoring of results and control of the camera trigger and reset of post-shift information. The vision system is composed of the camera and the controller and works applying computer vision tools, in this work we use a self-learning pattern identification tool that allowed us to obtain a higher quality degree in the test results from a group of images.